Selective action of human sera differing in fatty acids and cholesterol content on in vitro gene expression - Zirpoli, Hylde; Caputo, Mariella; Carraturo, Antonio; Torino, Gaetano; Fazio, Alessia; Attya, Mohamed; Rastrelli, Luca; Tecce, Mario Felice (Journal of cellular biochemistry, 2012)
Serum constituents might directly affect metabolic diseases pathogenesis and are commonly used as diagnostic tool. The aim of this study was to investigate the human serum effect on in vitro gene expression, related to nutrients action and involved in lipid metabolism. In detail, 40 human sera were firstly analyzed in fatty acids profile by gas‐chromatography. Then samples were tested through direct addition within culture medium on Hep G2 human hepatoma cells, comparing samples from hypercholesterolemic (average 273 mg/dl) versus normocholesterolemic male subjects (average 155 mg/dl), since this condition is a relevant disease risk factor and is typically consequent to nutritional style. Hypercholesterolemic sera produced a 0.4‐fold reduction of sterol regulatory element binding protein 1c (SREBP‐1c) mRNA (P < 0.05) and a 1.5‐fold increase of UDP‐glucuronosyltransferase 1A1 (UGT1A1) mRNA (P < 0.01). Samples with higher concentrations of n‐6 fatty acids produced a higher expression of UGT1A1 mRNA. Total fatty acids [docosahexaenoic, eicosopentanoic, arachidonic, linolenic, and linoleic acid (DHA, EPA, AA, LNA, and LA, respectively)] in each serum resulted roughly inverse with trend of SREBP‐1c mRNA expression. Serum AA, LA, and trans fatty acids were more abundant in hypercholesterolemic subjects (P < 0.01) while DHA as quota of detected fatty acids was significantly higher in normocholesterolemic subjects (P < 0.05). While it is not possible to indicate which component was responsible for the observed gene modulations, our data indicate that sera differing in lipid profiles, mainly associated with dietary behavior, differentially affect gene expression known to be involved in metabolic and nutritional related conditions. J. Cell. Biochem. 113: 815–823, 2012. © 2011 Wiley Periodicals, Inc.